Optimalisasi Keuntungan Digital Printing Menggunakan Branch and Bound serta Cutting Plane Berbasis R Software - Sekar Handayani; Achi Rinaldi; Siska Andriani (Universitas Negeri Gorontalo, 2022)
Digital printing is a procedure used to print patterns in modern printing using digital methods. In this study, what was discussed were banners, stickers, and invitations. This study aims to find the best method and obtain maximum profit resulting from production on CV Demangan Digital Printing by implementing the branch and bound method and the cutting plane method. The branch and bound method and the cutting plane method solve linear program problems with decision variables in integers. To help solve the case of optimizing the profitability of the digital printing business, the R software. Based on the results of the company's data analysis that has been carried out, it shows that the branch and bound method and the cutting plane method obtain the same maximum profit. The maximum profit obtained is Rp. 61.200.000 by producing 8000 meters of banners, 615 meters of stickers, and 500 invitations.